Fenomena Bankonka Dalam Drama Kazoku No Katachi Karya Shunichi Hirano - Adiyasa, I Putu Marta (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 2 No 2 (2020), 2020)
The title of this research is "The Phenomenon of Bankonka in Drama Kazoku No Katachi by Shunichi Hirano". This study aims to find out how the phenomenon of bankonka and its causal factors in the drama Kazoku No Katachi by Shunichi Hirano. This research uses the theory of literary sociology Wellek Warren, the theory of factors that cause bankonka by Tsutsui and the theory of semiotics by Danesi. This research uses descriptive analysis method. Based on the results of the study there were three figures who experienced the phenomenon of Bankonka, namely Daisuke, Sasaki and Hanako, which was shown through a late marriage and not thinking too much about marriage. Factors causing the Bankonka phenomenon in the drama Kazoku No Katachi are divided into two sexes, male and female. Factors causing the phenomenon of bankonka in men are 1) the happiness of living alone; 2) economic factors; 3) work factors; 4) hobby factors; 5) do not feel the benefits of marriage; 6) difficult to get a partner. Factors causing the phenomenon of bankonka in women are 1) work factors; 2) hobby factors.